Diets and trophic niches of the main commercial fish species from the Celtic Sea. Issue 5 (7th November 2017) - Rault, J.; Le Bris, H.; Robert, M.; Pawlowski, L.; Denamiel, M.; Kopp, D.
Abstract : The characterization and quantification of diets of nine commercially important Celtic Sea fish species (black‐bellied angler Lophius budegassa, blue whiting Micromesistius poutassou, Atlantic cod Gadus morhua, haddock Melanogrammus aeglefinus, European hake Merluccius merluccius, megrim Lepidorhombus whiffiagonis, European plaice Pleuronectes platessa, common sole Solea solea and whiting Merlangius merlangus ) was undertaken November 2014 and November 2015 to gain a better understanding of fish feeding strategies, prey preferences, competition for resources and, more generally, increases knowledge of marine ecosystem functioning. Prey were classified into 39 taxonomic groups. A feeding overlap index and multivariate analyses were used to classify the fishes into four main trophic groups where interspecific competition for resources may be important: piscivorous species, omnivorous species, planktivorous species and invertebrate benthic feeders. Ontogenetic changes in diet were also considered for L. budegassa, G. morhua, M. aeglefinus, M. merluccius and M. merlangus through partitioning into size classes. This revealed an important shift in the diet of M. merluccius from omnivory to piscivory, whereas M. aeglefinus exhibited no significant ontogenetic change in diet, remaining an invertebrate benthic feeder. Feeding strategies of these species were also investigated using the Shannon niche‐breadth index and other descriptors, such as the total number of taxonomic groups of prey and the mean number of prey in gut contents.